PENGARUH KEPEMIMPINAN CAMAT TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT KETUNGAU HILIR KABUPATEN SINTANG - Priska Risa Vitliani E.42008027 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this study is the Effect of Employee Performance Leadership Head Against The Head Office Ketungau Hilir of Sintang. The purpose of this study was to determine how much influence the performance leadership of district employees in the Office of the Head of Ketungau  Hilir  of Sintang.  This  research  is  quantitative  research  using product  moment correlation statistical test followed by calculating the coefficient of determination. The results showed a correlation of 0.913, which means very strong significance and count r> r table for error level of 5% and 1% (0.913> 0.708> 0.576) and the coefficient of determination of 83.3%. Based on the analysis of statistical data, indicators in this study are valid and variables are reliable. this means the hypothesis is accepted  that there is a positive  and significant correlation  between district leadership on employee performance. Keywords: Head Leadership, Employee Performance, Quality, Quantity, and Timeliness